Secondary benefits of the families improving together (FIT) for weight loss trial on cognitive and social factors in African American adolescents - Sweeney, Allison M. (Int J Behav Nutr Phys Act, 2019)
BACKGROUND: Although weight loss is an important primary outcome in obesity interventions, family-based interventions may have cascading ripple effects that extend to other aspects of health and well-being. Identifying these secondary benefits may be useful for understanding how to best engage underserved African American families in weight loss. The present research examines whether African American adolescents and parents perceive secondary benefits from participating in a family-based weight-loss intervention, including secondary health, social, or cognitive benefits. METHODS: Qualitative data were obtained from families participating in the group-based intervention of the Families Improving Together (FIT) for Weight Loss trial. During the final week of the face-to-face motivational and family-based intervention program, families completed a guided open-ended group discussion about changes they experienced from participating (14 groups, N = 41 adolescents and 41 parents). Sessions were audiotaped, transcribed, and coded by independent pairs of raters using both inductive and deductive approaches. Guided by the multi-theoretical framework for the FIT trial, some themes were determined prior to coding using a deductive approach, including: (a) health outcomes (e.g., monitoring strategies for diet and physical activity), (b) social outcomes (e.g., involvement in family support, group support, autonomy support, family bonding, positive communication) and (c) cognitive outcomes (e.g., expression of self-confidence through self-efficacy, self-regulation, establishment of long-term goals). In addition to these pre-determined themes, the coding process included an inductive assessment, allowing for unexpected themes to surface as well around positive self-talk, relapse prevention, and monitoring strategies for different types of weight-related behaviors. RESULTS: Across both adolescents and parents, the cognitive outcomes were the most frequently discussed outcomes, including self-regulation, monitoring strategies for diet, establishing long-term goals, and ultimate relapse prevention. Parents made a greater number of comments about the social outcomes, including family support, group support, self-efficacy, and family connectedness, whereas adolescents made a greater number of comments about positive family communication. CONCLUSIONS: The results provide preliminary support for the positive secondary effects of weight loss programs on improving both cognitive and social well-being in underserved African American adolescents. TRIAL REGISTRATION: ClinicalTrials.gov # NCT01796067. https://clinicaltrials.gov/ct2/show/NCT01796067?term=NCT01796067&rank=1 The trial was registered on February 21, 2013 and the first participant was enrolled July 12, 2013.